The Overview of Service Satisfaction Levels at the Internal Medicine Clinic of RSI PKU Muhammadiyah Pekajangan - Esti Rahayu; Wiwiek Natalya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Background: Patients' Satisfactions are the result of the patient's assessment and attitude towards the services that they received related to their expectations. Patients' satisfaction is one of the goals to be achieved by the hospital. The measurements of patient satisfaction are needed to be carried out to determine whether the performance of the hospital meet the patients' expectation or there is sti11 a need for an improvement of service quality. The Objective: This study aimed to describe the level of patients' service satisfaction at the Internal Medicine Clinic of RSI PKU Muhammadiyah Pekajangan based on five dimensions of patient satisfaction, namely tangible, reliability, responsiveness, assurance, and empathy. The Sample: This study involved 149 respondents at the Internal Medicine Clinic of RSI PKU Muhammadiyah Pekajangan. Methods: The design of this research was descriptive with a population of 1490. The sampling technique used was accidental sampling. The data analysis used univariate analysis. The Result: The results of this study indicated that the description of satisfaction from the five dimensions of satisfaction includes tangible in the internal medicine clinic, most of their satisfactions were very good (54 or 36.2%). The reliability with good satisfaction was 68 (45.6%). The responsiveness with very good satisfaction was 59 (39.5%). The assurance with good satisfaction was 64 (43%). Their empathies were mostly good satisfaction (53 or 35.6%). The Conclusion: The results of this study indicated that most of the respondents' satisfaction categories in the five dimensions of satisfaction (tangible, reliable, responsive, assurance, and empathy) were good.